Relationships between Plasma Micronutrients, Serum IgE, and Skin Test Reactivity and Asthma among School Children in Rural Southwest Nigeria. (25th May 2014) - Oluwole, Oluwafemi; Arinola, Olatunbosun G.; Adu, Mary D.; Adepoju, Adedayo; Adedokun, Babatunde O.; Olopade, Olufunmilayo I.; Olopade, Christopher O.
Abstract : Objective . Increasing prevalence of asthma has been attributed to changes in lifestyle and environmental exposures. We conducted a case-control study to investigate the relationship between serum micronutrients and asthma in rural school children in Nigeria. Methods . We administered questionnaires to 1, 562 children to identify children with asthma. Serum concentration levels of 12 micronutrients were determined in asthma cases (N = 37 ) and controls (N = 30 ). Allergy skin prick test and spirometry were also performed. Results . Plasma levels of the following micronutrients were significantly different between cases and controls: calcium (7.48 ± 2.16 versus8.29 ± 1.62 mg/dL;P = 0 . 04 ), manganese (44.1 ± 11.5 versus49.3 ± 7.9 mg/L;P = 0 . 01 ), selenium (76.1 ± 14.9 versus63.3 ± 26.8 μ g/L;P = 0 . 02 ), and albumin (3.45 ± 0.90 versus3.91 ± 0.99 g/dL;P = 0 . 04 ). Plasma concentrations of iron and selenium were positively correlated with lung function, r = 0.43 (P < 0.05 in each case) while manganese serum concentration was negatively correlated with asthma (r = - 0.44 ;P < 0.05 ). Conclusions . Children with asthma had reduced levels of plasma manganese, calcium, and albumin but raised level of selenium. The protective or risk effects of these micronutrients on asthma warrant further investigation.